SYSTEMATIC LITERATURE REVIEW ON THE APPLICATION OF UI/UX DESIGN METHODS IN SYSTEM DEVELOPMENT - Ramadani, Romi; Mahdiana, Deni (Informatika, Universitas Jenderal Soedirman, 2024)
In the current modern digital era, system development is undoubtedly rapid and massive, especially across various sectors such as healthcare, business, and public services. In system development, many aspects are considered, one of which is the appearance of the user interface. Interface design becomes an intriguing aspect and has an influence on system or application development. System development surely involves user interface and user experience aspects as part of the human-computer interaction (HCI) discipline. This research aims to identify research opportunities in UI/UX aspects in system development, with data obtained from relevant journals spanning from 2019 to 2024 as a representation of the latest study on UI/UX design research. This study utilizes the Systematic Literature Review (SLR) method. The results of this research provide a systematic literature review of existing studies on UI/UX design. This research can benefit the HCI community by applying methods in UI/UX design in system development to shape the direction of future research.